Investigating the knowledge of Rhetorical in Shafiee’s lyric poems - Omalbanin Nikkhahe Noori; Mostafa Salari; Behrooz Romiyani (مطالعات زبانی و بلاغی)
Rhetoric is one of the fields in which its artistic use has a prominent stand in the verse contexts. Each poet or writer has used it to beautify his work and attract the audience based on their needs. Shafiee is one of the poets who used the science of rhetoric thoroughly with complete coherence in his sonnets, and included the secondary intentions of each section well and carefully in his poems. He has put indicative and originative sentences by regarding to grammatical rules carefully and using knowledge of rhetoric in the interior of his sonnets. And he has made intelligible of what has considered as a secondary meaning. The use of Siege and palace beside the connection and season with sub-collections of each one has doubled the beauty of his sonnets. In this research, the author has used an analytical-descriptive method to extract exemplary evidence about the knowledge of rhetorical in the poet’s sonnets. The following attempt is made to introduce it in brief.